2009
DOI: 10.1016/j.ijdevneu.2009.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Hyperhomocysteinemia selectively alters expression and stoichiometry of intermediate filament and induces glutamate‐ and calcium‐mediated mechanisms in rat brain during development

Abstract: The aim of the present work was to investigate the actions of a chemically induced chronic hyperhomocysteinemia model on intermediate filaments (IFs) of cortical and hippocampal neural cells and explore signaling mechanisms underlying such effects. Results showed that in hyperhomocysteinemic rats the expression of neural IF subunits was affected. In cerebral cortex, glial fibrillary acidic protein (GFAP) expression was donwregulated while in hippocampus high and middle molecular weight neurofilament subunits (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 90 publications
1
2
0
Order By: Relevance
“…Moreover, a window of vulnerability of the cytoskeleton of hippocampal cells is evidenced, since misregulated phosphorylation is detected only at postnatal day 17 [30], reflecting an altered activity of the endogenous phosphorylating system associated with the IFs in this brain structure. As expected, NMDA receptors, L-VDCC and extracellular Ca In contrast with hypophosphorylation found in hippocampal slices, the chemically induced chronic hyperhomocysteinemia differently alters the signaling mechanisms directed to the cytoskeleton, producing PP1-, PP2A-and PP2B-mediated hypophosphorylation of NF subunits and GFAP in hippocampal slices of 17-day-old rats without affecting the cerebral cortex [31] through glutamate and Ca…”
Section: Hyperhomocysteinemia and The Cytoskeleton Of Neural Cellssupporting
confidence: 67%
“…Moreover, a window of vulnerability of the cytoskeleton of hippocampal cells is evidenced, since misregulated phosphorylation is detected only at postnatal day 17 [30], reflecting an altered activity of the endogenous phosphorylating system associated with the IFs in this brain structure. As expected, NMDA receptors, L-VDCC and extracellular Ca In contrast with hypophosphorylation found in hippocampal slices, the chemically induced chronic hyperhomocysteinemia differently alters the signaling mechanisms directed to the cytoskeleton, producing PP1-, PP2A-and PP2B-mediated hypophosphorylation of NF subunits and GFAP in hippocampal slices of 17-day-old rats without affecting the cerebral cortex [31] through glutamate and Ca…”
Section: Hyperhomocysteinemia and The Cytoskeleton Of Neural Cellssupporting
confidence: 67%
“…, activation of calcineurin, a Ca 2? -dependent protein phosphatase (Wang et al 2005), could be considered, since we have recently demonstrated Hcy-induced IF hypophosphorylation mediated by calcineurin in rat hippocampal slices (Loureiro et al 2009). …”
Section: Discussionmentioning
confidence: 99%
“…The study found that when the concentration of homocysteine increased, the rats will gradually increase growth and cognitive dysfunction, histopathology can also be found in hippocampal neurons atrophy, damage, and the nerve cells placed in high concentrations Homocysteine environmental culture will die, which is directly associated with high concentrations of homocysteine on the toxicity of nerve cells, this evidence was confirmed by Loureiro SO [11]; depression may also occur with low levels of folic acid , high levels of homocysteine, the mechanism is considered folic acid is an antioxidant that can remove oxygen free radicals, protect brain cells from free radical damage, maintain central nervous system function stability, and when folic acid Lack of hyperhomocysteinemia, oxygen free radicals increased, neuronal mitochondrial function damage, the brain antioxidant defense system imbalance, central nervous system dysfunction, causing the corresponding neuropathy and behavior abnormalities Known dysfunction [12].…”
Section: Water-soluble Vitaminsmentioning
confidence: 74%